158k views
0 votes
Factorise x^2-6x-55=0

User Hupperware
by
4.3k points

1 Answer

3 votes

Answer:

(x+5)(x-11)=0

Explanation:

x^2-6x-55=0

[Multiply the coefficient of last and first, (55*1=55) and find such a factor of it such that its product is equal to the product of coefficient of last and first and such that it adds or subtracts(11-5=6)(depending on the sign of last coefficient) up to the coefficient of middle term]

x^2-11x+5x-55=0

x(x-11)+5(x-11)=0

(x+5)(x-11)=0

User Drop Shadow
by
5.0k points